RBBR Model: A Prediction Model of Bank Health Level Based on Risk for Regional Development Banks (BPD) in Indonesia - Herizon Chaniago; Harry Widyantoro (Universitas Hayam Wuruk Perbanas, 2017)
The RBBR Model is a risk-based bank rating model. First of all, this study was conducted to find a model that can be used for predicting bank soundness and the level of bank health especially the Regional Development Banks (BPD) in Indonesia. Secondly, it tried to see the level of ability to moderate GCG variables on the relationship between bank business risk and bank soundness. Thirdly, it had to see the level of ability to mediate GCG variables on the relationship between bank profitability and bank soundness. This study used BPD in Indonesia as a population and all members of the population studied, thus it is a census study. The variables consist of business risk (liquidity risk, credit risk, market risk and operational risk), GCG score and earnings performance and capital performance as the independent variables and bank soundness as the dependent variable. The secondary data were collected by means of documentation method. Data analysis includes descriptive analysis and statistical analysis, to describe the results of research, and statistical analysis to answer the research problem. Statistical analysis PLS Warp and multiple linear regression analysis were used for analysis, and it was found that the model can be used to predict the health of BPD in Indonesia. Furthermore, GCG neither moderate the relationship between business risk and BPD health levels in Indonesia nor mediates the relationship between earnings performance and BPD health levels in Indonesia.